(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The objective of this work is to examine the more significant continuities and ruptures in the way of presenting and representing the intellectual and literary fields in the novels Las iniciales de la tierra and Las Palabras perdidas of the Cuban writer Jesus Díaz, as well as to analyze the relations that are established between them and the political field. The latter is particularly important because both productions deal with the Cuban revolution and its political program and because the period that they describe corresponds mainly to the decades of the 60s and the 70s, years in which politics constituted the main norm of legitimacy of the textual grammars.